1998
DOI: 10.1002/(sici)1097-4644(19980101)68:1<1::aid-jcb1>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field exposure enhances mRNA expression of σ32 in E. coli

Abstract: The mechanism of interaction between weak electromagnetic fields and cells is not understood. As a result, the health effect(s) induced by exposure to these fields remains unclear. In addition to questions relating to the site of initial magnetic field (MF) interactions, the nature of the cell's response to these perturbations is also unclear. We examined the hypothesis that the cells respond to MFs in a manner similar to other environmental stressors such as heat. Using the bacterium Escherichia coli, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…The unexpected effect of magnetic field exposure on DNA stability prompted us to further our investigation in order to find out the mechanism involved. In this regard, research of Cairo et al [10] showing that when E. coli cultures are exposed to a magnetic field (60 Hz) of 1.2 mT, the expression of δ 32 , a transcription factor that guides RNA polymerase to interact with a variety of stress gene promoters, would be enhanced directed us to consider the potential role of heat shock proteins. As a matter of fact, there were three lines of research results that had inspired us.…”
Section: Resultsmentioning
confidence: 99%
“…The unexpected effect of magnetic field exposure on DNA stability prompted us to further our investigation in order to find out the mechanism involved. In this regard, research of Cairo et al [10] showing that when E. coli cultures are exposed to a magnetic field (60 Hz) of 1.2 mT, the expression of δ 32 , a transcription factor that guides RNA polymerase to interact with a variety of stress gene promoters, would be enhanced directed us to consider the potential role of heat shock proteins. As a matter of fact, there were three lines of research results that had inspired us.…”
Section: Resultsmentioning
confidence: 99%
“…LI‐EMF induced a total of 188, 63, and 60 transcription factors in the treated samples with recovery times of 0 h, 3 h, and 6 h. As the time increased after LI‐EMF treatment, the number of elicited transcription factors declined significantly, which indicated that the transcription factor repaired the influence of LI‐EMF on the cells of I. lacteus . Cairo et al [] found that ELF‐MF (1.1 mT, 60 Hz) could stimulate the δ 32 expression, a stress promoter transcription factor in E. coli . In addition, several glutathione S‐transferases (GSTs), generated under diverse stress conditions [Collinson and Grant, ], were elicited by LI‐EMF in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Two pieces of information are consistent with this hypothesis. First, Cairo et al, [1998] have shown that the intracellular level of mRNA speci®c for s 32 , a protein that interacts with RNA polymerase to help it recognise a variety of stress promoters in the cells, is enhanced under electric ®eld conditions. Second, our results of electrophoretical analysis of total cell proteins have shown quantitative and qualitative differences between protein pro®les obtained out of sham and bacteria growing under electric ®eld conditions [Grzesiuk et al, 2000;Laubitz et al, 2000].…”
Section: Discussionmentioning
confidence: 99%